Appropriateness of Ticagrelor Use at Initiation: A Population-Based Cohort Study - Jean-Pierre Gregoire; Paul Poirier; Norma Pérez; Éric Demers; Jocelyne Moisan (Frontiers Media S.A., 2018)
Purpose. Ticagrelor is recommended following an acute coronary syndrome if used appropriately. Its use has not yet been well described in the context of ambulatory clinical practice. The objective of this study was to assess the proportion of ticagrelor new users who initiated this medication appropriately and explore associated factors. Methods. A retrospective population-based inception cohort study was conducted using Quebec administrative databases. The study population included all Quebec residents aged ≥18 years who had a first ticagrelor prescription claim between 1 January, 2012, and 31 March, 2015, and had been continuously eligible in the Quebec public drug plan during the 365 days preceding the first ticagrelor claim. The initial ticagrelor prescription was considered appropriate if:1) it met the indication for use criterion, 2) the prescribed daily dose was 90 mg twice a day, and 3) there was a concomitant use of acetylsalicylic acid (ASA) 80-81 mg daily. Factors potentially associated with the ticagrelor appropriateness of use were included in a logistic log-binomial regression model. Results. A total of 7,073 patients were included in the study, 6,013 (85.0%) had an appropriate indication, 6,895 (97.5%) were prescribed ticagrelor 90 mg twice a day, and 6,385 (90.3%) had a concomitant prescription of ASA. A total of 5,371 (75.9%) patients were prescribed ticagrelor in accordance with all criteria. Twelve factors were associated with prescription appropriateness. Conclusions. A large majority of patients initiated ticagrelor appropriately. Further improvement in appropriateness may come at targeting indication for use.